(untitled) (Research, Society and Development, 2021)
The objective of this scoping review protocol is to identify and synthesize the scientific evidence produced on the use of Integrative and Complementary Health Practices (PICS) by the elderly in primary health care services (PHC). The review will follow the method proposed by the Joanna Briggs Institute, which establishes five steps: 1) identification of the research question; 2) identification of relevant studies; 3) selection of studies; 4) data analysis; and 5) grouping, synthesis and presentation of data. To formulate the research question, the Participants (P) strategy was used: elderly; Concept (C): Integrative and Complementary Practices in Health; Context (C): Primary Health Care. Thus, the research question formulated included the PCC (Participants-Concept-Context): What is the scientific evidence, in the context of PHC (P), of the use of PICS (C) by the elderly (P) for the promotion, maintenance and recovery of health, and for the prevention of injuries? Controlled descriptors were selected from the Health Sciences Descriptors (DeCS), Medical Subject Headings Section (MeSH), EMTREE and CINAHL Headings. It is expected that this scoping review will provide a mapping of the use of PICS by the elderly, as a method for health promotion, disease prevention, in addition to the maintenance and recovery of health and, therefore, providing healthy and quality aging, in order to provide the performance of the PHC as a gateway to the Unified Health System with great resolving capacity.